Nanoscale Imaging of High‐Field Magnetic Hysteresis in Meteoritic Metal Using X‐Ray Holography - R. Blukis; B. Pfau; C. M. Günther; P. Hessing; S. Eisebitt; J. Einsle; R. J. Harrison (Geochemistry, Geophysics, Geosystems, 2020)
Abstract Stable paleomagnetic information in meteoritic metal is carried by the “cloudy zone”: ~1–10 μm‐wide regions containing islands of ferromagnetic tetrataenite embedded in a paramagnetic antitaenite matrix. Due to their small size and high coercivity (theoretically up to ~2.2 T), the tetrataenite islands carry very stable magnetic remanence. However, these characteristics also make it difficult to image their magnetic state with the necessary spatial resolution and applied magnetic field. Here, we describe the first application of X‐ray holography to image the magnetic structure of the cloudy zone of the Tazewell IIICD meteorite with spatial resolution down to ~40 nm and in applied magnetic fields up to ±1.1 T, sufficient to extract high‐field hysteresis data from individual islands. Images were acquired as a function of magnetic field applied both parallel and perpendicular to the surface of a ~100 nm‐thick slice of the cloudy zone. Broad distributions of coercivity are observed, including values that likely exceed the maximum applied field. Horizontal offsets in the hysteresis loops indicate an interaction field distribution with half width of ~100 mT between the islands in their room temperature single‐domain state, providing a good match to first‐order reversal curve diagrams. The results suggest that future models of remanence acquisition in the cloudy zone should take account of strong interactions in order to extract quantitative estimates of the paleofield.